2016
DOI: 10.1089/scd.2016.0073
|View full text |Cite
|
Sign up to set email alerts
|

From Early Embryonic to Adult Stage: Comparative Study of Action Potentials of Native and Pluripotent Stem Cell-Derived Cardiomyocytes

Abstract: Cardiomyocytes (CMs) derived from induced pluripotent stem cells (iPS-CMs) are promising candidates for cell therapy, drug screening, and developmental studies. It is known that iPS-CMs possess immature electrophysiological properties, but an exact characterization of their developmental stage and subtype differentiation is hampered by a lack of knowledge of electrophysiological properties of native CMs from different developmental stages and origins within the heart. Thus, we sought to systematically investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 43 publications
4
17
0
Order By: Relevance
“…Nonetheless, our hiPSC-CMs are still in the early stage of development and are structurally immature ( Figure 1 B) compared with adult cardiomyocytes. Excitation-contraction coupling studies on hiPSC-CMs at day 30 post differentiation ( Figures 1 D–1G) suggest that they straddle along the embryonic to neonatal stage as seen in other studies ( Lundy et al., 2013 , Peinkofer et al., 2016 ). Cardiac μGMEA electrophysiological data reported in this study also demonstrate electrical maturational plasticity.…”
Section: Discussionsupporting
confidence: 75%
“…Nonetheless, our hiPSC-CMs are still in the early stage of development and are structurally immature ( Figure 1 B) compared with adult cardiomyocytes. Excitation-contraction coupling studies on hiPSC-CMs at day 30 post differentiation ( Figures 1 D–1G) suggest that they straddle along the embryonic to neonatal stage as seen in other studies ( Lundy et al., 2013 , Peinkofer et al., 2016 ). Cardiac μGMEA electrophysiological data reported in this study also demonstrate electrical maturational plasticity.…”
Section: Discussionsupporting
confidence: 75%
“…Studies investigating iPSC-CM metabolism have also found iPSC-CM have a fetal phenotype. iPSC-CMs utilize glucose to meet its energy demands whereas adult CMs preferentially use fatty acids oxidation [37,[143][144][145][146]216].…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of iPSC-CM metabolism shows that they mostly rely on glucose and amino acids and to a lesser extent on fatty acids whereas in adult CMs, the dominant metabolic pathway is fatty acid oxidation [143][144][145][146]. Figure 1 compares the different metabolic substrates and pathways used by iPSC-CMs and adult CMs.…”
Section: Metabolic Propertiesmentioning
confidence: 99%
“…Unfortunately, due to our inability to standardize working antibodies for atrial and nodal subtypes during this project, it was not possible to report whether such shift can also be verified in the molecular level. However, it could be argued that the parameters that support AP classification into different subtypes would only be valid during a limited period of development, rather than throughout the entire cardiogenesis, with eventual (and confounding) overlapping of AP properties (112). Moreover, it has been proposed that the AP kinetic parameters fail in efficiently clustering differentiated hiPSC-CM into discrete subpopulations (64).…”
Section: Analysis Of the Proportions Of Atrial Ventricular And Nodalmentioning
confidence: 99%
“…The functionality of ion channel matures as in vivo cardiogenesis progresses (113)(114)(115) and this culminates in electrophysiological alterations on AP kinetic parameters (112).…”
Section: Analysis Of Time-dependent Variations In Ap Kineticsmentioning
confidence: 99%